The maculosus group of the genus Celaenorrhinus Hübner, 1819 from China, with discovery of female C. kuznetsovi Devyatkin, 2000 (Lepidoptera: Hesperiidae: Pyrginae) - Huang, Zhen-Fu; Chiba, Hideyuki; Fei, Wen; Fan, Xiao-Ling (Zootaxa, 2014)
The maculosus group of the genus Celaenorrhinus from China is reviewed, in which 7 species are treated. Taiwanese maculosus taiwanus is reinstated to full species rank. The hitherto unknown female of C. kuznetsovi, as well as the female genitalia of C. maculosus and C. major are described. Adults and genitalia are illustrated, and a brief description of each species is given. A Key to the Chinese species of the maculosus group is provided.